2021
DOI: 10.1038/s41598-021-90300-9
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis on correlation of weather with COVID-19

Abstract: This study presents a systematic review and meta-analysis over the findings of significance of correlations between weather parameters (temperature, humidity, rainfall, ultra violet radiation, wind speed) and COVID-19. The meta-analysis was performed by using ‘meta’ package in R studio. We found significant correlation between temperature (0.11 [95% CI 0.01–0.22], 0.22 [95% CI, 0.16–0.28] for fixed effect death rate and incidence, respectively), humidity (0.14 [95% CI 0.07–0.20] for fixed effect incidence) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 36 publications
4
32
0
Order By: Relevance
“…In addition, meteorological data have been suggested as additional factors that influence viral spread [26][27][28][29][30][31]. A recent systematic review suggested that, among meteorological factors, temperature and humidity were significantly correlated with COVID-19 morbidity [32]. In other studies, parameters related to policy, pollution levels, and wind speed were also included, which may also be considered as potential factors [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, meteorological data have been suggested as additional factors that influence viral spread [26][27][28][29][30][31]. A recent systematic review suggested that, among meteorological factors, temperature and humidity were significantly correlated with COVID-19 morbidity [32]. In other studies, parameters related to policy, pollution levels, and wind speed were also included, which may also be considered as potential factors [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…There is an increased application of statistics not only in biomedical fields [20] but also in fields like environmental or atmospheric sciences where researchers still use scatter plots or regression to determine correlation between one prime feature vs one or multiple other features [21]. It can be challenging to find confounders, features that seem to be highly correlated with a prime feature as a cause or effect of association with another feature highly correlated with a prime feature.…”
Section: Impactmentioning
confidence: 99%
“…Similarly, another systematic review showed a negative correlation between SARS-CoV-2 infection incidence and temperature and humidity in most studies ( Briz-Redón and Serrano-Aroca, 2020 ). The first meta-analysis on this topic found significant correlations between temperature, humidity and wind speed with SARS-CoV-2 infection incidence ( Majumder and Ray, 2021 ). A more recent systematic review found a negative association between temperature and humidity with SARS-CoV-2 mortality in the majority of studies ( Romero Starke et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%